The Effectiveness of Character Education Based on Religion and Culture: Case Study in Vocational High Schools - Mirzon Daheri; Wakhudin; Hadi Prayitno; Wajnah; Fauzi Aldina (International Journal of Educational Research Excellence (IJERE), 2024)
The study of Aqidah has been found to be of great importance in the education of students. The scope of Aqidah that allows students to form noble morals will result in them becoming qualified humans in all aspects of life. From the perspective of Aqidah, which plays a role in the formation of human morals, it can be said that humans can avoid despicable morals as a manifestation of the teachings of Islamic Aqidah. The morals derived from the Qur'an and hadith serve as the foundation for the development of spiritual values, which in turn produce quality generations. Aqidah and morals are inextricably linked; noble morals serve as a reflection of a person's personality and can elevate one's status. Moral education can be considered a form of moral education within the context of Islamic education. The objective of this study is to examine the learning of moral creed among students at XYZ School, and to assess the efficacy of this learning in fostering the formation of religious character. The study employs a multi-methodological approach, including observational techniques, in-depth interviews, and the analysis of documentary materials. The results of the study indicate that the implementation of moral creed learning at XYZ School has a significant impact on fostering the realization of student morals. The cultivation of character education is a value that should be embraced as a foundation of nationhood, as it serves as a cornerstone for Indonesian children to cultivate the requisite qualities to thrive as citizens of a nation, in alignment with the character values that are reflective of the nation's cultural heritage.. It is a highly effective approach that enables students to learn how to have morals towards themselves, to parents, to fellow friends, and to the wider community, which can be applied in everyday life.